Interplay of financial inclusion and economic growth in emerging economies - Shreya Pal; Shravni Vankila; Melvin Norbert Fernandes (World Development Sustainability)
This study delves into the complex link between financial inclusion—both traditional and digital—and economic growth across emerging economies from 1990 to 2022, using Dynamic Simulated ARDL and Driscoll-Kraay Standard Error techniques. Key findings highlight that traditional financial inclusion correlates positively with economic growth, whereas digital financial inclusion presents obstacles. Additionally, fiscal, monetary, and trade policies play vital roles: fiscal policies in Brazil, Colombia, and Mexico focus on infrastructure, social programs, and tax reforms, respectively, to spur growth. Monetary policies include Brazil's inflation targeting, Turkey's interest rate adjustments, and India's MUDRA scheme, which promotes entrepreneurship. Trade policies, such as Chile's Free Trade Agreements and Mexico's participation in NAFTA, improve market access and economic resilience, while Egypt and Saudi Arabia focus on foreign direct investment and economic diversification.The study emphasizes coordinated policy efforts for sustained growth, advocating for financial inclusion supported by robust regulations and government investments in critical areas like infrastructure and healthcare. Central banks contribute by maintaining price stability and credit access, while strategic trade agreements and export diversification enhance economic resilience. The focus of the study on emerging economies and macro-level insights calls for further research at the micro-level to refine these results. By maintaining policy coherence and regular evaluations, these strategies aim to foster inclusive, long-term economic growth.